Molly Haynes: capstone - Haynes, Molly, artist (Colorado State University. Libraries, 2023)
The artist's statement: Clay is material that holds memory; memory of its shape, the artists' mark, the collective moment in time, of where it has been, how it has traveled and its purpose. It holds the memories of ancestral stories, how people have thrived or survived. In its fired state, clay holds the memory of the practice and the process. It tells so many different stories, nourishing the body, representing the body, containing the body. "Her Spirit" is about memory, each feather a representation of motherly spirit, essence and the memories we hold. The shadows they make are not unlike a memory; intangible and existing only because the form exists somewhere in time. They are a reminder of loss and grief but also grace and beauty. Attached to the physical body of the vessel, the feathers become weighted and grounded. They become personal, bodily, and intimate. The forms represent an opposition between spirit and physical. The spirit of the feather, a collection of personal memories, lives simultaneously in the ether and the body, where one is formless and eternal and the other is bound by change. I am interested in creating forms that can be in dialog with each other and their process. By creating molds that I use to create slip-cast hanging feathers and pressmolded sprigs to attach on vessels, the hanging feathers and vessels are in conversation with representation of spirit. These vessels include abstracts owl-like forms that portray the embodiment of spirit. They are glazed and textured in ways to elicit owl-ness. The feathers are suspended in the air, cascading to the ground yet frozen in time. My intention is to create a moment where each feather is a memory and suspended together become a network of memories. The feathers are intended to be in dialog with the feathers on the pots, because they are not separate from each other, but a part of a larger microcosm of collective memories that we all have with the people we love. They are glazed or unglazed, white stoneware and porcelain, since they are the original pure memory before the memory gets diluted over time. During the process of creating the feathers, many shatter, some break, some never make it through to completion because they are so delicate in their bone-dry state before they are fired. In the right light the feathers create many shadows on the walls. Not unlike a memory, a shadow is elusive and intangible, representative of something that exists but is not the thing itself.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery